Effectiveness of The Internet of Things (IoT)-Based Jigsaw Learning Model on Students' Creative Thinking Skills: A- Meta-Analysis - Dewanto Dewanto; Hasyim Mahmud Wantu; Yanurita Dwihapsari; Tomi Apra Santosa; Ika Agustina (Postgraduate, University of Mataram, 2023)
This study aims to determine the effectiveness of the Internet of Things (IoT)-based Jigsaw learning model on students' creative thinking skills. This research is meta-analysis research. The data sources in this study come from 19 national and international journals published in 2020-2023. Literature search process through Google Scholar, Eric, Springer, ScienceDirect, Sage journal, and ProQuest. Data collection techniques are direct observation and documentation through the journal database. Inclusion criteria are articles or proceedings indexed by SINTA and WOS. Research is in the form of experiments or quasi-experiments. Research is related to the Jigsaw and IoT learning models on students' creative thinking skills and has complete data to be able to calculate the effect size (ES). Data analysis is a quantitative analysis with the help of the JSAP application. The results showed that the average effect size (ES = 0.882) was very high dengan nilai p < 0.05. These findings explain that the Internet of Things (IoT)-based jigsaw learning model has a significant influence on students' creative thinking skills. Furthermore, the IoT-based jigsaw model helps teachers be more creative in conveying subject matter to students.